Amputation rates of the lower limb by amputation level - observational study using German national hospital discharge data from 2005 to 2015 - Melissa Spoden; Ulrike Nimptsch; Thomas Mansky (BMC, 2019)
Abstract Background In international comparisons, rates of amputations of the lower limb are relatively high in Germany. This study aims to analyze trends in lower limb amputations over time, as well as outcomes of care concerning in-hospital mortality and reamputation rates during the same hospital stay which might indicate the quality of surgical and perioperative health care processes. Methods This work is an observational population-based study using complete national hospital discharge data (Diagnosis-Related Group Statistics (DRG Statistics)) from 2005 to 2015. All inpatient cases with lower limb amputation were identified and stratified by eight amputation levels. Time trends of case numbers and in-hospital mortality were studied age-sex standardized. For inpatient cases with reamputation during the same hospital stay, first and last amputation levels were cross tabulated. Results A total of 55,595 amputations of the lower limb in 2015 (52,096 in 2005) were identified. After age-sex standardization to the demographic structure of 2005, a relative decrease of − 11.1% was revealed (men − 2.6%, women − 25.0%). The stratified analysis by amputation levels showed that the decreases were induced by higher amputation levels, whereas the amputation levels of toe/foot ray after standardization still showed a relative increase of + 12.8%. In-hospital mortality of all cases with lower limb amputation fell from 19.8% in 2005 to 17.4% in 2015 (SMR 0.89 [95% CI 0.86; 0.92]). The percentage of reamputations during the same hospital stay declined from 13.2 to 10.2%. Conclusions The number of lower limb amputations declined in Germany, however distinctly stronger in women than in men. The observed decreases of in-hospital mortality as well as of reamputation rates point to improvements in perioperative health care. Despite these indications of improvements, the distinct increase in case numbers at the level of toe/foot ray calls for additional targeted prevention efforts, especially for patients with diabetes.